2023
DOI: 10.1007/s00586-023-07567-x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of anterior lumbar interbody fusion (ALIF) versus posterior lumbar interbody fusion (PLIF), transforaminal lumbar interbody fusion (TLIF), posterolateral lumbar fusion (PLF)

Abstract: Purpose The rate of elective lumbar fusion has continued to increase over the past two decades. However, there remains to be a consensus on the optimal fusion technique. This study aims to compare stand-alone anterior lumbar interbody fusion (ALIF) with posterior fusion techniques in patients with spondylolisthesis and degenerative disc disease through a systematic review and meta-analysis of the available literature. Methods A systematic review was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Open lumbar fusion is the traditional procedure for the treatment of lumbar spondylolisthesis, but this procedure requires extensive stripping of soft tissues such as the lumbar muscles and prolonged distraction, which leads to nerve damage and insu cient blood supply to the paravertebral muscles, thus increasing the incidence of chronic pain [10][11]. The paravertebral muscles are critical for supporting spinal extension, maintaining lumbar lordosis and achieving dynamic spinal stability, so the risk of medically induced injury to the paravertebral muscles should be minimized during surgery [12][13]. The development of spinal endoscopic techniques has brought new opportunities for the treatment of lumbar spondylolisthesis, offering new possibilities for patients to achieve faster and more effective rehabilitation by providing more precise observation and manipulation in a minimally invasive manner [14].…”
Section: Discussionmentioning
confidence: 99%
“…Open lumbar fusion is the traditional procedure for the treatment of lumbar spondylolisthesis, but this procedure requires extensive stripping of soft tissues such as the lumbar muscles and prolonged distraction, which leads to nerve damage and insu cient blood supply to the paravertebral muscles, thus increasing the incidence of chronic pain [10][11]. The paravertebral muscles are critical for supporting spinal extension, maintaining lumbar lordosis and achieving dynamic spinal stability, so the risk of medically induced injury to the paravertebral muscles should be minimized during surgery [12][13]. The development of spinal endoscopic techniques has brought new opportunities for the treatment of lumbar spondylolisthesis, offering new possibilities for patients to achieve faster and more effective rehabilitation by providing more precise observation and manipulation in a minimally invasive manner [14].…”
Section: Discussionmentioning
confidence: 99%
“…Hoy et al, in a randomized clinical trial, through comparing PLF and TLIF in terms of post-operative functional outcomes, showed comparable improvement rates, with no statistical difference in daily function, work, leisure, or anxiety [21]. In another recent extended systematic review, summarizing data from 21 studies with 3686 patients, TLIF and PLF procedures showed similar improvement in terms of patient-reported outcomes [22]. Nevertheless, in reviewing the literature regarding fusion rates following both procedures, a slightly significant difference favoring TLIF surgery is presented [6,19,23].…”
Section: Introductionmentioning
confidence: 98%
“…Transforaminal lumbar interbody fusion (TLIF) has become a commonly used surgical technique for these conditions, providing relief by relieving pressure and stabilizing the afflicted parts of the spine. The achievement of a stable spinal fusion is crucial for the success of TLIF [ 3 , 4 , 5 ], and this outcome is impacted by several factors such as patient characteristics, surgical technique, and the choice of fusion materials. Traditionally, autografts have been considered the most reliable method for spinal fusion because of their ability to promote bone formation, stimulate bone growth, and provide a scaffold for new bone tissue [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%